Peran Manajemen Resiko Dalam Meningkatkan Pengembangan Usaha Toko Nevia - Chintya, Neha; Shintiya, Ayu; Ramadhana, Royhan Zaki; Situmorang, Daffa C Zein; A, Arsyadona (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Risk management has an important role in business development, including for Nevia Stores. This research aims to analyze the role of risk management in supporting the business development of Nevia Stores. The research method used was qualitative with a case study approach, where data was obtained through information owner of the Nevia Shop. The research results show that implementing effective risk management can help Nevia Stores identify, analyze and control various risks that might hamper operations and business growth. Some of the risks faced include financial, operational and market competition risks. By implementing good risk management, Toko Nevia can minimize potential losses and create a more sustainable business development strategy.